2020
DOI: 10.1177/2325967119896104
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Release of the Adductor Longus With or Without Sports Hernia Repair Is a Useful Treatment for Recalcitrant Groin Strains in the Elite Athlete

Abstract: Background: Chronic strain and/or tendinopathy of the adductor longus tendon can be a cause of long-standing groin pain in the elite athlete, resulting in significant time lost from competition. Accurate diagnosis and treatment can expedite return to play. Purpose/Hypothesis: To evaluate return to sport and performance in National Collegiate Athletic Association (NCAA) Division I football players and National Football League (NFL) players following adductor longus release with or without sports hernia repair. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…There is conflicting evidence in the literature regarding game use and performance following surgical treatment of AP in professional sports. 15,17,25 Jack et al 25 compared 56 NFL players who underwent surgical treatment of AP to a control group, finding that those in the surgery group played in significantly fewer seasons (3.8 AE 2.4 vs 3.2 AE 2.1 years) and GPS (14.0 AE 2.3 vs 12.0 AE 3.4) after RTP; however, they found no difference in performance between groups. 25 A retrospective review of NFL combine participants (mean age 22.1 years old) with a history of surgical treatment for AP was conducted by Knapik et al, 17 who found no significant impact on GPS, GS, draft status, roster activity, or number of seasons played.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence in the literature regarding game use and performance following surgical treatment of AP in professional sports. 15,17,25 Jack et al 25 compared 56 NFL players who underwent surgical treatment of AP to a control group, finding that those in the surgery group played in significantly fewer seasons (3.8 AE 2.4 vs 3.2 AE 2.1 years) and GPS (14.0 AE 2.3 vs 12.0 AE 3.4) after RTP; however, they found no difference in performance between groups. 25 A retrospective review of NFL combine participants (mean age 22.1 years old) with a history of surgical treatment for AP was conducted by Knapik et al, 17 who found no significant impact on GPS, GS, draft status, roster activity, or number of seasons played.…”
Section: Discussionmentioning
confidence: 99%
“…Although the adductor complex has been surgically addressed in comprehensive open surgeries for athletic pubalgia (or core muscle injury), a recent study reports similar successful outcomes in afflicted athletes using surgery "targeted" to ENDOSCOPIC REPAIR OF PROXIMAL ADDUCTOR AVULSION e3 the specific pathologic area such as the adductor origin. 5 But if, for example, a pubic plate avulsion is found on endoscopic examination, endoscopic repair has been described 8 and can be performed seamlessly with endoscopic adductor repair. Furthermore, recalcitrant femoroacetabular impingement and osteitis pubis, which may occur concomitantly, may be addressed with hip arthroscopy for the former and endoscopic pubic symphysectomy 7 for the latter condition.…”
Section: Discussionmentioning
confidence: 99%
“…1 Good outcomes have been reported with conservative and surgical treatments. [2][3][4] In contrast to relatively common adductor tendinopathies which, when recalcitrant and treated surgically with tenotomy (partial or complete), 5 retracted avulsion injuries have been treated with open repair of the retracted tendon using suture anchor fixation. 3,4 This Technical Note presents a completely endoscopic reattachment of a severe grade 3 proximal adductor avulsion with >3 cm retraction (Fig 1) at 6 weeks after acute eccentric injury.…”
mentioning
confidence: 99%
“…Players sustaining adductor muscle injuries and matched controls were identified using publicly available injury data via previously established methods. 8,9,[11][12][13][14][15][16][17]31 Sources for injury reports included official team websites, injury reports, official team press releases, personal websites, and professional statistical websites. Injury reports from public media platforms were manually cross-referenced with official league reports by 2 authors (O.L.-G. and S.P.).…”
Section: Player Identificationmentioning
confidence: 99%